Voluntary contributions to a public good when partial contribution is a dominant strategy - Claudia Keser (Institute for Advanced Studies (IHS), 1995)
We present an experiment on voluntary contributions to a public good. The game has a dominant strategy solution in the interior of the strategy space. In the experiment we observe significant over-contribution. This result is similar to those of the typical corner solution experiments. – – Wir beschreiben eine experimentelle Untersuchung zu freiwilligen Beiträgen zu einem öffentlichen Gut. Das dem Experiment zugrunde liegende Spiel hat eine Lösung in dominanten Strategien, die im Inneren des Strategieraums liegt. Im Experiment beobachten wir signifikant überhöhte Beiträge. Dieses Experiment entspricht den Ergebnissen der typischen Experimente mit Randlösung.
Keywords: C92; H41; 330; experimental economics; public goods